BARRIERS TO EXCLUSIVE BREASTFEEDING PRACTICES AMONG HIV-POSITIVE MOTHERS ATTENDING POSTNATAL CLINIC AT KAJJANSI HEALTH CENTRE IV, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Namyalo, Victoria; Bukenya, Bonny; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2025)
Background Exclusive breastfeeding is critical for infant health, particularly among HIV-positive mothers. This study aimed to assess the barriers to exclusive breastfeeding among HIV-positive mothers attending a postnatal clinic at Kajjansi Health Center IV. Methodology A descriptive cross-sectional study design was employed to select 40 mothers. A simple random sampling method was used, and data was collected using a semi-structured researcher-administered questionnaire with both open and close-ended questions. Microsoft Excel was used for data analysis. Results 40 respondents participated in this study; the majority, 28(70%) of the respondents, were between 18-25 years of age, while only 01(2.5%) was above 35 years. 75% of the respondents knew that exclusive breast milk is important for HIV-positive mothers. However, 37.5% of the mothers were not sure whether taking ARVs during pregnancy and after childbirth reduces the chances of HIV transmission to the born baby, and 37.5% of them also mentioned replacement feeding as the ideal baby feeding method in the first 6 months. 62% of the respondents reported having sufficient breast milk for EBF. However, 65% of them reported sometimes having support from their partners to EBF, and 20% were not sure whether EBF is culturally accepted. Half of the mothers never got breastfeeding counseling during ANC, and 75% were not advised on EBF for the first 6 months at the health facility. Conclusion The study found good knowledge among most of the respondents. However, socioeconomic and health facility factors greatly contributed to barriers to EBF among HIV-positive mothers. Recommendation The government, through the Ministry of Health, should expand breastfeeding education during antenatal care and postnatal visits, emphasizing the health benefits of EBF beyond HIV transmission alone.